Effect of different acids surface treatments and thermocycling on shear bond strength of composite resin to feldspathic ceramic - Ammar A Lateef (College of Dentistry/ University of Baghdad, 2014)
Background: the aim of this study was to evaluate the effect of different surface acids treatments (37%phospjoric acid, 5%hydrofluoric acid, 1.23 acidulated phosphate fluoride) of feldspathic ceramic VITA 3D MASTER , and the effect of thermocycling on shear bond strength using a ceramic repair kit (ivoclar/vivadent). Material and Methods: sixty Nickel-Chromium metal base plates were prepared(9mm diameter,3mm depth) using lost wax technique, 2mm thick layer of ceramic(VITA 3D MASTER) fused to metal plates, all specimens were embedded in acrylic resin blocks except their examined surfaces and divided into 3 main groups 20 specimens each, Grp A: treatment with 37%phosphoric acid for 2 mins, Grp B: etching with 5% hydrofluoric acid for 2mins, Grp C: etching with 1.23% acidulated phosphate fluoride for 10 mins; monobond-plus, heliobond, resin composite(Tetric EvoCeram) were applied to each specimen according to manufacturer's instruction using transparent split mold(5mm diameter, 4 mm height); specimens were stored in 37OC distilled water for 12 weeks, 10 specimens of each group were subjected to thermocycling between 5 oC and 55 o C for 800 cycles with 30s dwell time; shear bond strength was determined by a universal testing machine (instron 1122) at a cross head speed 0.5mm/min; One way ANOVA test, LSD test and student-t test were used to analyze shear bond strength. Results: Mean shear bond strength values for the tested groups were: A1= 11.650.68 Mpa, A2=10.880.58 Mpa, B1=17.930.41 Mpa, B2=17.420.35 Mpa, C1=15.170.61 Mpa, C2=14.510.48 Mpa ; one way ANOVA test showed highly significant difference among groups; LSD test revealed that the use of 5% HF for ceramic surface treatment(GB) was highly significant than the treatment with 37%PA(GA) or 1.23%APF(GC) respectively and the use of 1.23%APF(GC) was highly significant than the use of 37%PA(GA); Student t- test showed a significant difference between subgroups of the same group with and without thermocycling. Conclusion: ceramic surface treated with 5% HF acid for 2 mins recorded the highest shear bond strength, followed by surface treatment with 1.23% APF for 10 mins, most specimens treated with 5%HF showed cohesive failure with in ceramic while specimens treated with 1.23%AFP showed more (adhesive/cohesive) failure than adhesive or cohesive alone, and specimens treated with 37% PA showed nearly 50:50 adhesive and combination failure, thermocycling reduced the bond strength of each group significantly